Pemodelan Hujan - Aliran Daerah Aliran Sungai Rokan Dengan menggunakan Data penginderaan Jauh - Mardhotillah, Mutia; Sutikno, Sigit; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Data availability for modeling usually become a problem because of incompleteness and imprecision data. The development of knowledge and the advancement of technology progress encourage the development of hydrological modeling by using remote sensing data. This research conducted rainfall-runoff modeling using remote sensing data in Rokan watershed, Riau Province. To utilize remote sensing data, a special software namely Integrated Flood Analysis System (IFAS) is used in this research. IFAS is a remote sensing program that was developed by a research institution of the Japanese public works called the International Centre for Water Hazard and Risk Management (ICHARM). IFAS was used to model the rainfall-runoff in Rokan watershed with four types of different periods simulation and calibration. Rainfal-runoff period from 1 January 2003 until 31 December 2006, 1 January 2004 until 31 December 2006, 1 January 2005 until 31 December 2006 and 1 January 2006 until 31 December 2006 was used for this modeling and then was validated with period data of 2004 and 2005. The results become optimal after the calibration process period of two years and one year data. The two years period have the correlation (R) value 0,627, volume error (VE) 1,007%, and the coefficient of efficiency (CE) 0,615 and the one year period the correlation (R) value 0,663, volume error (VE) 3,30%, and the coefficient of efficiency (CE) 0,759. Â Keywords: rainfall-runoff modeling, satellite data, IFAS, calibration, validation